Kajian Modernisasi atas Pembaharuan Islam Nurcholish Madjid - husen, muhammad nur; numan, moh; Hayeemaming, Marwan; laili, afrohatul (LPPM UNU BLITAR, 2023)
Nurcholis Majid is an Islamic thinker who has had a strong and broad influence in the history of Indonesian Islamic intellectualism. His thoughts had a very broad impact on Islamic religious life, and more than that, he even became a reference and direction for Indonesian Muslim intellectuals. One proof of how strong Nurcholis Majid's influence is is that he succeeded in developing intellectual discourse among Islamic society in a modern, open and democratic way. The type of research carried out by the researcher is normative legal research, because the researcher uses library materials as the main data to analyze cases, this research specifically examines Nurcholish Madjid's Study of Islamic Reform. Modernization according to Nurcholis Madjid means rationalization, namely to obtain maximum efficiency in thinking and working, for the happiness of mankind is an imperative and fundamental command of God. Modernization means thinking and working according to fitrah and Sunnatullah (divine law) which is haq (because nature is haq).